Continuum Composition - Ottavi, Julien; Pickett, Jenny; Haug, Vonrik; Malaise, Chloé; Héraud, Julien; Loret, Vincent; Plastre, Robin; Valdivia, Marco; Koutsomichalis, Marinos; Kitsis, Andreas; Theodosiou, Antonis (My University, 2022)
For this new composition, Dime Ensemble invites electronic musicians from Bergen, Lima and Limassol to join a common Glocal performance in one single orchestral network music symphony. The ChaosOrchestra is playing a new collective online performance with visuals and sound experimentation through the network. Dime Ensemble is entering the force of Chaoslab with a performance in shared virtual space, joining outer-space inside cables transmission. Experimentation in signal production join the beyond through inter-connected physical space.